Konten Meme Marketing untuk Memitigasi Kelelahan Media Sosial dan Meningkatkan Niat Beli Generasi Z - Fadhil Adiyatma; Ratih Amelia (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to evaluate how meme marketing content influences social media fatigue and subsequent purchase intentions among Generation Z TikTok users in Indonesia. Utilizing a quantitative approach within a causal research design, data were gathered via a web-based questionnaire from 137 sampled individuals aged 17 to 25. The empirical data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) within the SmartPLS software environment. The findings revealed that meme marketing content exerts a significant negative effect on social media fatigue (β = −0.258, t = 3.832, p < 0.001), indicating that humorous marketing material effectively mitigates users' cognitive exhaustion. Furthermore, meme marketing content demonstrated a significant positive effect on purchase intention (β = 0.459, t = 5.318, p < 0.001). Conversely, social media fatigue showed neither a significant direct effect on purchase intention (β = −0.120, t = 1.532, p = 0.126) nor a significant mediating role between meme marketing content and purchase intention (β = 0.031, t = 1.267, p = 0.205). These findings suggest that meme marketing is an effective strategy to reduce digital fatigue while simultaneously driving purchase intentions among Generation Z consumers on TikTok